2019
DOI: 10.2174/1871530319666190119101058
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Lipid Profile, Hepatic and Renal Antioxidant Activities, and Markers of Hepatic and Renal Dysfunctions in Alloxan-Induced Diabetic Rats by Virgin Coconut Oil

Abstract: Background: Research studies that holistically investigated the effect of administration of Virgin Coconut Oil (VCO) on diabetic humans or animals are limited in literature. Objective: To investigate the effect of administration of VCO on lipid profile, markers of hepatic and renal dysfunction, and hepatic and renal antioxidant activities of alloxan induced diabetic rats. Methods: Twenty-four male albino rats were used, and they were divided into four groups of six rats each. Group 1 (Normal Control, NC) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
4
7
1
Order By: Relevance
“…We found that virgin and filtered coconut oils, coconut water, coconut milk and metformin have all improved lipid profile by decreasing total-, LDL-, VLDL-cholesterols, and triglycerides and by increasing HDL-cholesterol in diabetic rats. In agreement with our findings, treatment of alloxan-Induced Diabetic Rats by virgin coconut oil resulted in a reduction in diabetes induced total-, LDL-, VLDL-cholesterols, and triglycerides ( Eleazu et al 2019 ). In a randomised trial, coconut oil significantly increased HDL-cholesterol and significantly decreased LDL-cholesterol ( Khaw et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that virgin and filtered coconut oils, coconut water, coconut milk and metformin have all improved lipid profile by decreasing total-, LDL-, VLDL-cholesterols, and triglycerides and by increasing HDL-cholesterol in diabetic rats. In agreement with our findings, treatment of alloxan-Induced Diabetic Rats by virgin coconut oil resulted in a reduction in diabetes induced total-, LDL-, VLDL-cholesterols, and triglycerides ( Eleazu et al 2019 ). In a randomised trial, coconut oil significantly increased HDL-cholesterol and significantly decreased LDL-cholesterol ( Khaw et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, following the treatment with coconut products the levels of these urinary parameters drastically lowered in diabetic rats, emphasizing the potential of these coconut products to reverse the effects of diabetes. In comparison to our data, it is shown that alloxan-Induced diabetic rats had significantly reduced urea, creatinine, uric acid after treatment with virgin coconut oil ( Eleazu et al 2019 ). Likewise, virgin coconut oil attenuated maximum physical activity-induced increase in urea, uric acid and creatinine in rats ( Sinaga et al 2019 ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Following alloxan injections, a significant increase in FBG of alloxan-induced diabetic animals in comparison to NC+H2O, NC+VCO, and ATZ rats was noted. Similarly, several studies have documented a marked increase in blood glucose levels following alloxan induction [25,31,35,36,37]. It was observed that treatment of the diabetic group with 10ml/kg of VCO for two weeks brought about a significant drop in fasting blood glucose levels.…”
Section: Estimation Of Serum Insulin Concentrationmentioning
confidence: 90%
“…Lastly, 50 μl of Stop Solution was then added to each well which changes the color from blue to yellow, and the intensity of the color is measured at 450 nm. [31]. Triggering the production of reactive oxygen species (ROS), which in turn cause the destruction of the beta cells and eventually result in a condition of insulindependent diabetes, has been documented as the primary mechanism of action of alloxan-induced diabetes [32].…”
Section: Estimation Of Serum Insulin Concentrationmentioning
confidence: 99%